Reseña analítica de la literatura sobre el pensamiento gerencial en las empresas constructoras, enfoques y tendencias (2015)
The article is concentrated on the second phase of the research project and focuses on 20 titles of management, analysis and review, directly related to the management thinking of managers of Construction Companies in Colombia which provides certificated information on lines orientation of its management emphasis and identifies the dominant trends in the management environment, from which it is possible a theoretical approach in order to address the problems of the organizational environment of the construction companies. It contains a count and a balance of theoretical and conceptual elements of strategic thinking as a first approximation for the construction of the theoretical framework of the Management of Construction Companies, necessary condition for addressing the problems of Organizational Environment Construction Companies.